Legal Analysis of Daughters' Inheritance Mahjub Siblings According to Ibn Abbas - Fajriyyah, Latifatul; Maulana, Muhammad (PT. Riset Press International, 2025)
In the decision of the Panel of Judges with Case Number 247/Pdt.P/2020/PA.Smd, only the wife and daughter of the Heir are entitled to inherit the inheritance. The Heir's brothers and sisters are hindered from inheriting by the daughter. Meanwhile, this provision differs from the provisions in fiqh, which do not mention siblings who may inherit together with daughters. This study aimed to analyze the decision of the Samarinda Religious Court in case Number 247/Pdt.P/2020/PA.Smd and to find out why the Judge took the opinion of Ibn 'Abbas and overruled the opinions of other Ulama. This study uses a qualitative research method with a normative legal approach. The study results explain that the Panel of Judges determined case no. 247/Pdt.P/2020/PA.Smd concerning the determination of heirs where a daughter obstructs the inheritance rights of a sibling of the Heir, referring to the Supreme Court Jurisprudence Number 86 K/AG/1994, as well as inheritance provisions concerning the principle of hijab-mahjub in Book II Revised Edition 2013, which contains the legal principle